2005
DOI: 10.1159/000085841
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Functioning after Discontinuation of Long-Term Growth Hormone Treatment in Girls with Turner Syndrome

Abstract: It is common practice in the case of Turner syndrome (TS) to treat short stature with GH treatment and to induce puberty with estrogens at an age as close to normal puberty as possible. This approach in most cases leads to a height in the normal range in childhood, adolescence, and adulthood in TS. Little data is available, however, on its effect on psychosocial functioning. In the present study, we evaluated psychosocial functioning in a group of 50 women with TS, after reaching final height in two multicente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 57 publications
3
32
0
1
Order By: Relevance
“…Our findings are globally in line with the YASR data reported by van Pareren et al [13] revealing comparable behavioural problem scores between TS women and the general population. However, their results were only based upon the broad-band scales.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are globally in line with the YASR data reported by van Pareren et al [13] revealing comparable behavioural problem scores between TS women and the general population. However, their results were only based upon the broad-band scales.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding self-perception, TS patients had self-perception scores comparable to the reference group on the majority of subscales except for social acceptance, romantic relations and sense of humour, globally in line with the Dutch results [13], but somewhat in contrast to other previous studies reporting impaired self-esteem and self-confidence [4, 6, 27, 29]. Problems in social relationships, particularly in contact with the opposite sex, as reflected by a lesser number of intimate relationships or marriages, later psychosexual milestones, problems with social cues have repeatedly been reported [4,5,6,7,8,9, 18].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Such studies have shown that a delayed induction of puberty may have long-lasting effects on sex life (Carel et al, 2006) and that, even though height and pubertal treatments result in what is considered 'normal' height and puberty induction at a 'normal' age, the women affected may still present psychological difficulties because of the treatment (Carel et al, 2005;van Pareren et al, 2005). It has also been reported that Canadian girls and young women with TS score significantly lower when measuring general, social, and appearance-related self-esteem, but do not differ from women without Turner Syndrome when it comes to performance-related self-esteem (Cragg and Lafreniere, 2010).…”
Section: Previous Research On Turner Syndrome and Uterine And Vaginalmentioning
confidence: 99%
“…Quanto ao momento apropriado para início da terapia de substituição hormonal ovariana, ainda que existam evidências para postergá-la com ganho adicional na altura pelo retardo do fechamento epifisário, a instituição de GHr por período suficientemente prolongado, antecedendo a idade cronológica de 12 anos, aparentemente não modifica, de modo significativo, o prognóstico estatural (24,25).…”
Section: Tratamento Com Hormônio De Crescimento Recombinante (Ghr)unclassified